الأبعاد الفنية والتربوية في قصص الأطفال الإلكترونية موقع قصص أطفال قبل النوم أنموذجا - عزوز آية الرحمان; بريش, ريحاب; بحري كوثر; بن خليفة لميس; مني مروة (University of Eloued جامعة الوادي, 2024)
تهدف هذه "الأبعاد الفنية والتربوية في قصص الأطفال الإلكترونية (موقع قصص أطفال قبل النوم)، إلى استنطاق الأبعاد التربوية والتعليمية من القصص الإلكترونية الموجهة للطفل، كما تعتبر قصص الأطفال الإلكترونية وسيلة من وسائل السرد تحتويها صور وفيديوهات وصوت الراوي، تهدف إلى فعالية وتبسيط أحداث القصة لإيصال المعلومة للقارئ الطفل تحت إطار تشويقي فعال. This "artistic and pedagogical dimensions of e-children's stories (bedtime children's stories site), aims to derive educational and educational dimensions from child-oriented e-stories. E-children's stories are also seen as a means of narrating images, videos and narrators' voices, aiming at the effectiveness and streamlining of story events to communicate information to the child reader under an effective promotional framework. Children are easy to receive and imitate from electronic stories. These media play a major role in building or
مذكرة. ليسانس
Keywords: قصص، الأطفال، الأبعاد، الفنية- التعليمية، الوسائط، البنية.; Stories; Children; Dimensions; Technical-Educational; Media; Structure